Pendekatan Ekologi Media Solo Radio FM: Upaya Mempertahankan Eksistensi di Tengah Transformasi Digital di Surakarta - Salwa, Akrimy Naila; Triyono, Agus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The rapid advancement of technology has led to the emergence of new media, such as the internet with various platforms, making it easier for people to access information and entertainment. This has resulted in a decline in interest in radio. Nevertheless, Solo Radio FM continues to strive to maintain its existence. The purpose of this study is to analyze the application of Ecology Media theory to Solo Radio FM in sustaining its presence. This research employs a qualitative method with a descriptive approach and utilizes the Ecology Media theory introduced by Dimmick and Rouhtenbuhler, which involves three main elements: type of content, type of audience, and capital. The findings show that Solo Radio FM maintains its existence by producing broadcast programs divided into information and entertainment categories favored by listeners. In terms of audience, Solo Radio FM segments its listeners and expands its reach through social media. Lastly, regarding capital, Solo Radio FM pays attention to the financial aspect by optimizing revenue from advertising.